Pengorganisasian dan Pengembangan Ide - Ignatius Harjanto (Magister Scientiae, 2011)
Writing requires what to write and how to write it. Having ideas only cannot guarantee people to be able to write their ideas. Ideas must be organized and developed in such a way to help readers understand. Effective writers organize and develop their ideas effectively. They use different strategies to sort the ideas and information they have gathered in order to make connections, identify relationships, and determine possible directions and forms for their writing. This article discusses issues of organizing and developing ideas. Starting with a theory of essay writing, the article discusses the parts of an article and its contents. For clarity, examples of organizing and developing ideas are given